Perempuan Pakpak dalam Realitas Adat (Studi kasus di desa Pegagan Julu VIII) - Hadriana Marhaeni Munthe (Universitas Negeri Medan, 2018)
This paper is derived from case studies conducted on Pakpak women by cross-strata and status in domestic family institutions and customary institutions as public institutions in the village of Pegagan Julu VIII with qualitative feminist methods. The feminist method emphasizes the research process that involves women through their life experiences in cases of indigenous marginalization experienced by them in their communities. Sources of data from women's life experiences which are also voiced by women themselves. Data collection techniques used FGD (Focus Group Discussion), in-depth interviews and participant observation of women who became research informants. The results of the study show that Pakpak women are cross-social strata with the potential to be indigenous conservationists, ironically, the reality is not directly proportional to their authority or authority to make decisions in any customary or customary work. The reason is that the dominance of patriarchal culture which is still strong in prioritizing men and lacking respect for women has influenced the weak bargaining position of women. The consequences that arise are that most customary practices and values are less pro-women, both at the family level and in the community. They experience exploitation especially from the poor strata, so that the poverty that is already heavy is faced by women, the more the burden of adat that must be borne by women. As a result women have the potential to experience double poverty (double poverty) and even tend to experience situations of alienation from their customs.